Comparison of the microbiology and antibiotic treatment among diabetic and nondiabetic patients hospitalized for cellulitis or cutaneous abscess. Issue 12 (30th September 2014) - Jenkins, Timothy C.; Knepper, Bryan C.; Jason Moore, S.; Saveli, Carla C.; Pawlowski, Sean W.; Perlman, Daniel M.; McCollister, Bruce D.; Burman, William J.
<x xml:space="preserve">Abstract</x> BACKGROUND Among diabetics, complicated skin infections may involve gram‐negative pathogens; however, the microbiology of cellulitis and cutaneous abscess is not well established. OBJECTIVE To compare the microbiology and prescribing patterns between diabetics and nondiabetics hospitalized for cellulitis or abscess. DESIGN Secondary analysis of 2 published retrospective cohorts. SETTING/PATIENTS Adults hospitalized for cellulitis or abscess, excluding infected ulcers or deep tissue infections, at 7 academic and community facilities. METHODS Microbiological findings and antibiotic use were compared among diabetics and nondiabetics. Multivariable logistic regression was performed to identify factors associated with exposure to broad gram‐negative therapy, defined as receipt of at least 2 calendar days of β‐lactamase inhibitors, second‐ to fifth‐generation cephalosporins, fluoroquinolones, carbapenems, tigecycline, aminoglycosides, or colistin. RESULTS Of 770 total patients with cellulitis or abscess, 167 (22%) had diabetes mellitus. Among the 38% of cases with a positive culture, an aerobic gram‐positive organism was isolated in 90% of diabetics and 92% of nondiabetics (P = 0.59); aerobic gram‐negative organisms were isolated in 7% and 12%, respectively (P = 0.28). Overall, diabetics were more likely than nondiabetics to be exposed to broad gram‐negative therapy (54% vs 44% of cases, P = 0.02). By logistic regression, diabetes mellitus was independently associated with exposure to broad gram‐negative therapy (odds ratio: 1.66, 95% confidence interval: 1.15‐2.40). CONCLUSION In cases of cellulitis or abscess associated with a positive culture, gram‐negative pathogens were not more common among diabetics compared with nondiabetics. However, diabetics were overall more likely to be exposed to broad gram‐negative therapy suggesting this prescribing practice may not be not warranted. Journal of Hospital Medicine 2014;9:788–794. © 2014 Society of Hospital Medicine